Evaluation of the radiosurgical treatment of cerebral arteriovenous malformations: a retrospective single-center analysis of three decades. (26th September 2019) - Hirschmann, Dorian; Goebl, Philipp; Witte, Frederic H; Gatterbauer, Brigitte; Wang, Wei-Te; Dodier, Philippe; Bavinzski, Gerhard; Ertl, Adolf; Marik, Wolfgang; Mallouhi, Ammar; Roetzer, Thomas; Dorfer, Christian; et al.
Abstract : Background: Gamma Knife radiosurgery (GKRS) in the treatment of arteriovenous malformations (AVMs) is still controversially discussed. Objective: To present long-term follow-up data on patients after Gamma Knife radiosurgery for cerebral AVMs. Methods: Overall, 516 patients received radiosurgery for cerebral AVMs between 1992 and 2018 at our department, of whom 265 received radiosurgery alone and 207 were treated with a combined endovascular-radiosurgical approach. Moreover, 45 patients were treated with a volume-staged approach. Two eras were analyzed, the pre-modern era between 1992 and 2002 and the modern era thereafter. Results: In GKRS-only treated patients, median time to nidus occlusion was 3.8 years. Spetzler–Ponce (SP) class was a significant predictor for time to obliteration in the whole sample. Median time to obliteration for the combined treatment group was 6.5 years. Patients in the pre-modern era had a significantly higher obliteration rate than those treated in the modern era. Overall, the calculated yearly hemorrhage risk in the observation period after first GKRS was 1.3%. Permanent post-radiosurgical complications occurred in 4.9% of cases but did not differ between the treatment groups or treatment eras. The obliteration rate was significantly lower and the hemorrhage rate was higher in volume-staged treated patients than in conventionally treated patients. Conclusion: GKRS is an effective treatment option for SP class A and B cerebral AVMs. After combined endovascular-radiosurgical treatment, the outcome of selected SP class C AVMs aligns with that of SP class B lesions. Both the combined therapy and radiosurgery alone constitute sound methods for treatment of cerebral AVMs.